Bombay brokers - Björkman, Lisa, 1977- (Duke University Press, 2021)
"Bombay Brokers collect thirty-six character profiles of men and women whose knowledge and labor--which is often seen as morally suspect--are essential for navigating everyday life in Bombay, one of the world's most complex, dynamic, and populous cities."--